2023
DOI: 10.2147/oaem.s411096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contact-Restricted Basic Life Support Training During the Nation’s Contact Restriction Policy on Learning Outcomes

Abstract: Objective Basic life support (BLS) training aimed at building knowledge and skills in cardiopulmonary resuscitation. During training, there is the possibility of airborne COVID-19 transmission. The aim was to evaluate students’ knowledge, skills, and course satisfaction following contact-restricted BLS training under the contact restriction policy. Methods From July 2020 to January 2021, a prospective, descriptive study was conducted among fifth-year dental students. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Various formats of online training exist, including those incorporating pre-training and post-training assessments, interactive video modules, virtual reality simulations, nonpresential practical sessions using mannequins with automated real-time feedback and assessments conducted at 3 and 6 months. [31][32][33][34] A study conducted in China, exploring knowledge and attitudes towards AED usage, identified key barriers. Lack of proficiency in resuscitation techniques and limited practical skills were identified as significant impediments.…”
Section: Open Accessmentioning
confidence: 99%
“…Various formats of online training exist, including those incorporating pre-training and post-training assessments, interactive video modules, virtual reality simulations, nonpresential practical sessions using mannequins with automated real-time feedback and assessments conducted at 3 and 6 months. [31][32][33][34] A study conducted in China, exploring knowledge and attitudes towards AED usage, identified key barriers. Lack of proficiency in resuscitation techniques and limited practical skills were identified as significant impediments.…”
Section: Open Accessmentioning
confidence: 99%